The effect of yeast (Saccharomyces cerevisiae) fermentation on amino acid composition of hot water extract of Ficus capensis leaf - Uche, Dennis-Eboh; Onyeukwu, Onyeka Benjamin; Ajoh, Alfred Ikechukwu; Ohwokevwo, Oghenenyore Andy; Apiamu, Augustine; Egbune, Egoamaka O.; Achuba, Fidelis I; George, Betty O (African Journal of Tropical Medicine and Biomedical Research, 2024)
Introduction: In this study, the amino acid composition of cold and hot water extracts of Ficus capensis leaf was examined, along with the impact of yeast fermentation on the amino acid composition of the hot water extract. Although the hot water extract of Ficus capensis is commonly consumed as a beverage locally, there is currently a lack of documented literature regarding the amino acid composition of the wine produced from this extract. Materials and Methods: Cold and hot water extracts of Ficus capensis leaf was extracted using homogenization and decoction method respectively. Ficus capensis wine was produced from hot water must prepared using 0.8 g/l yeast, 22 brix, at pH 4.5 and fermented for 9 days. The amino acid composition of the cold water, hot water and wine extracts of Ficus capensis leaf were assessed using High Performance Liquid Chromatography. Results: The result shows the presence of amino acids in the cold water, hot water and wine extract of Ficus capensis. However, the wine contained more amino acids with methionine an essential amino acid having the highest concentration. Conclusion: Fermentation of the hot water extract should be encouraged since it improved the amino acid content of the wine produced and would serve as an additional raw material for wine industry. Moderate consumption of Ficus capensis wine could potentially be beneficial to health and as well as combat the problem of malnutrition.